Creation of community and identity in the new towns of Shanghai - Harry den Hartog (Materia Arquitectura, 2010)
The contemporary concept of “new town” is based on nuclei that function independently. Analogous to the Garden City of Ebenezer Howard (1898) and to the soviet planning, these new towns should be self-sufficient. Although most of the new towns and satellite cities in the world prove that a planned city needs a long time to acquire life, recent examples in Shanghai promise to surpass occidental cases and become living communities. This is a product of the especial combination of state planning and the growing freedom of developers and inhabitants. Together with the success stories there are also failures, something inevitable in an urban laboratory.